Predesign Methodology of Voltage Inverters Using a Gradient-Based Optimization Algorithm - Voldoire, Adrien; Schanen, Jean-Luc; Ferrieux, Jean-Paul; Sarrazin, Benoit; Gautier, Cyrille (IEEE journal of emerging and selected topics in power electronics, 2021)
This article presents an optimization process applied to the sizing of high-power silicon carbide inverters. The case study is the design of an aeronautical converter. A gradient-based optimization method is chosen for its ability to explore a wide solution space with a large amount of constraints, which is the case during the predesign phase. Many topologies are selected and the associated models are developed. Among all these models, active and passive component design and spectral analysis of voltages and currents are presented. The optimization results, with the goal of minimizing the global mass of the converter, are provided. The different topologies are compared to find the best one for the selected case study. The relevance of the optimization result is evaluated with the study of the optimality of the solution. Finally, the experimental results are compared with the optimization ones, which validates the good accuracy of analytical models.